Triton-X-100: Green Media for Aza and Thia-Michael Addition - Yadav, Veena; Lagarkha, Rekha; Kumar, Rupesh (Asian Journal of Chemistry, 2010)
Triton-X-100 (non-ionic) is found to be an inexpensive and nontoxic reaction medium as well as catalyst for aza and thia-Michael addition under milder and neutral reaction conditions at room temperature. This eco-friendly protocol offers the ease of operation, avoid the use of acid and base catalysts for this conversion, no side reactions observed and moreover can be recovered and recycled.